TEACHING ENGLISH VOCABULARY THROUGH BRAINSTORMING TECHNIQUE; IN THE SDIT AL –HASANAH - Akbar Kurtubi Amraj (Universitas Pamulang, 2022)
research has many problems to teach in elementary school in the first grade in order the teacher prepares the subject before teaching and prepare physic and mental. The methodology applied in this research is qualitative, to analyse the problems of the study in a specific way by approaching the subject of the problems in a natural way. For these reasons, the qualitative approach is applied in this research is to explore the teaching English vocabulary and brainstorming technique. The research exploration is expected to present the real picture in a detailed view of the obstacles in students’ vocabulary mastery gathered from teaching English vocabulary and brainstorming technique in the research findings.In this research the researcher discusses about teaching vocabulary by using brainstorming technique to manage the students becomes a good students. An another teacher gave suggestion to use brainstorming technique, It can help a teacher and the students to learn vocabularies in the same role. So, the technique for teaching vocabularies is use brainstorming, because the technique can help the students to learn and memorize vocabulary easy and can help the teacher to explain easily.The objective of this research is to know the effectiveness of teaching English Vocabulary through Brainstorming Technique. The research was conducted at the first grade of SDIT Al-Hasanah Tangerang. Keywords: Teaching Vocabulary, Brainstorming Technique